The Effect of Worried Doll Therapy on Pre-School Age Anxiety Levels With Hospitalization In Rumkital Dr. Ramelan Surabaya - Dedi Irawandi (Journal of Global Pharma Technology, 2020)
Background: Play therapy is an effort to change problematic behavior by placing children in play situations. Anxiety is a pathological condition characterized by feelings of fear accompanied by somatic signs, a sign of a hyperactive autonomic nervous system. The aim of this study was to analyze the effectiveness of "Worried Doll" play therapy on the level of anxiety in preschool children with hospitalization in Navy Hospital Dr. Ramelan Surabaya. Materials and Methods: The study design was a quasi-experimental approach Non-equivalent Control Group with a total of 204 research respondents preschool children are cared for in Rumkital Dr. Ramelan Surabaya. The results showed that playing “worried doll” therapy was effective in reducing the level of anxiety in pre-school age children who experienced hospitalization. Results: Based on the results of the statistical test in the intervention group, the P value was 0.007